Strengthening Grievance Redress System: A Case of Narsingdi District Administration (Bangladesh Journal of Public Administration, 2024)
Grievance Redress System (GRS) is one of the critical social accountability tools for ensuring accountable and people-friendly Public Administration of Bangladesh. For ensuring quality service delivery and accountability, Cabinet Division introduced GRS in 2007. Subsequently, in 2014, online GRS was designed to modernize and update the management of existing system, under the supervision of the Cabinet Division. The purpose behind the initiative was to redress the citizens’ grievances effectively and timely. Moreover, Cabinet Division published a guideline in 2015 on GRS. Finally, second version of GRS software was hosted in 2018 for establishing user-friendly online GRS in the Ministries/Divisions and subordinate offices. Present study was carried out to assess the current status of implementation of Online GRS in the district level government offices of Bangladesh alongside its potential challenges. In order to attain the research objectives qualitative approach was followed in this study. Semi-structured questionnaire, in-depth interview, observation, Key Informant Interview and Focus Group Discussion methods were used to collect primary data while all relevant sources were used to collect secondary data. The study revealed that the implementation status of GRS in the field level government offices was its infancy. The service providers were not properly following the guidelines of GRS and they were found busy with other state functions and less attentive in strengthening the GRS system. There were stumbling blocks in implementing the system including a small number of complaints submission, institutional incapacity, lack of proper monitoring and evaluation etc. Lack of public awareness was one of the leading causes of poor implementation of GRS. The research has come up with the conclusion that institutionalization of awareness building program, capacity development of the service providers, establishing a separate legal Authority of GRS under Cabinet Division and result-based monitoring and evaluation are essential to better outcome of GRS.